2015
DOI: 10.1139/cjpp-2014-0500
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial miRNA (MitomiR): a new player in cardiovascular health

Abstract: Cardiovascular disease is one of the major causes of human morbidity and mortality in the world. MicroRNAs (miRNAs) are small RNAs that regulate gene expression and are known to be involved in the pathogenesis of heart diseases, but the translocation phenomenon and the mode of action in mitochondria are largely unknown. Recent mitochondrial proteome analysis unveiled at least 2000 proteins, of which only 13 are made by the mitochondrial genome. There are numerous studies demonstrating the translocation of prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 95 publications
1
63
0
Order By: Relevance
“…In contrast, TnT mutants demonstrated significant differences in expression in 48% (44 of 92) of miRNAs: 16 miRNAs were upregulated more than 2-fold and 28 were downregulated more than 2-fold when compared with their littermate controls (control-T) ( Figure 5 and Supplemental Figure 2). Several of these differentially expressed miRNAs have been previously implicated in cardiac hypertrophy, cardiac fibrosis, apoptosis, mitochondrial function, and autophagy ( Figure 6) (51,(57)(58)(59). Thus, our miRNA-seq analysis revealed global changes in miRNA expression in TnT mutants, but only limited changes in MyHC mutants.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…In contrast, TnT mutants demonstrated significant differences in expression in 48% (44 of 92) of miRNAs: 16 miRNAs were upregulated more than 2-fold and 28 were downregulated more than 2-fold when compared with their littermate controls (control-T) ( Figure 5 and Supplemental Figure 2). Several of these differentially expressed miRNAs have been previously implicated in cardiac hypertrophy, cardiac fibrosis, apoptosis, mitochondrial function, and autophagy ( Figure 6) (51,(57)(58)(59). Thus, our miRNA-seq analysis revealed global changes in miRNA expression in TnT mutants, but only limited changes in MyHC mutants.…”
Section: Resultsmentioning
confidence: 76%
“…A remarkable result of our study is the global changes in miRNA expression present in TnT but not in MyHC mutants, many of which involved differentially expressed miRNAs that have been implicated in cardiac hypertrophy, fibrosis, apoptosis, mitochondrial function, and autophagy (51,(57)(58)(59). To assess whether differences in miRNA biogenesis could underlie our results in TnT mutants, we examined mRNA levels of factors involved in miRNA processing, including Drosha, DGCR8, Exportin-5, Dicer, TRBP, PACT, and Argonaute, and found no significant changes in either of the mutants, when compared with littermate controls (Supplemental Table 2).…”
Section: Discussionmentioning
confidence: 93%
“…The association of a miRNA with the RNA-induced silencing complex (RISC) has been shown in the cytoplasm, with the Argonaute (AGO) family proteins functioning to help in miRNA repression through the inhibition of protein synthesis when bound to the 3′-untranslated region of the mRNA [6,39]. A variety of groups, including our own, has also indicated the presence of miRNA in the mitochondria [3,5,1315,27,28,50,55,8385, 89,98]. MiRNA species have the ability to target mRNA transcripts produced by the mitochondrial genome in the mitochondrion to control mRNA stability and degradation [27,28,33].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are involved in the regulation of gene expression through RNA silencing and post-transcriptional gene silencing via binding to the 3'-untranslated region (3'-UTR) of specific mRNAs (11,12). miRNAs regulate diverse aspects of development and physiology, such as metabolic diseases (13), cardiovascular disease (14,15), immune dysfunction (16,17) and cancer (18,19). A large number of studies have reported that miRNAs are key factors in regulating cell differentiation and growth, migration, apoptosis and necrosis.…”
Section: Introductionmentioning
confidence: 99%